West Sumatran Stingless Bees (Hymenoptera: Apidae: Meliponini): What can be told from its Local Distribution. Issue 1 (May 2021) - Herwina, H; Salmah, S; Jasmi,; Yaherwandi,; Mairawita,; Janra, M N; Rusdimansyah,; Christy, B Y; Sari, D A; Putri, G
Abstract: Research on stingless bee at several Meliponiculture (stingless beekeeping) sites in West Sumatra, including at Universitas Andalas Campus Complex, had been conducted from April to December 2019 by using direct survey and direct collection methods on stingless bee worker at their colony entrances. A total of 18 stingless bee species that belong to five genera were collected. Tetragonula was the genus with the highest in species number (8), followed by Homotrigona (5) and Lepidoptrigona (3). Meanwhile, Heterotrigona and Geniotrigona were only represented by a single species each despite their popularity among West Sumatra beekeepers. Universitas Andalas Campus Complex harbours the highest species number of stingless bee (10), followed by stingless beekeeping site in Lubuk Minturun (7). Only 2-4 stingless bee species bred elsewhere stingless beekeeping sites. We presume that the difference of species number recorded in various stingless beekeeping sites indicated the complexity of this bee species within the variety of habitats.